An Exploration of Figurative Language in Henry Moodie’s Song Album Mood Swings - Gea, Pinta Kesadaran; Pasaribu, Tiara Kristina; Sembiring, Rony Arahta (UIR Press, 2026)
Figurative language plays a fundamental role in song lyrics as it enables songwriters to convey complex emotions, personal experiences, and deeper meanings beyond literal interpretation. This study aims to identify the types of figurative language found in Henry Moodie's song album Mood Swings and to explain how those figurative expressions are realized within the lyrics. This research employs a descriptive qualitative method. The data were collected from the lyrics of thirteen songs in the album, obtained from Spotify, and analyzed using Perrine's (1992) theory of figurative language. The findings reveal that five types of figurative language are found in the album, namely metaphor, simile, personification, symbol, and hyperbole, with a total of 40 instances identified. Symbol appears as the most dominant type with 10 instances, followed by hyperbole (9), metaphor (8), personification (7), and simile (6). The analysis demonstrates that each type serves a distinct expressive function in conveying emotional depth and personal experience throughout the lyrics. These findings indicate that figurative language is not merely a stylistic device in Henry Moodie's songwriting but a fundamental means of communicating emotional truth. This study is expected to contribute to the understanding of figurative language in song lyrics and to serve as a reference for students, researchers, and educators in the fields of linguistics and literary studies.